Beyond autonomous regions: measuring communal self-governance - Koos, Agnes Katalin; Keulman, Kenneth (Frontiers in Political Science, 2025)
The most venerable cross-national measure of inter-group political inequality, brought about by the Ethnic Power Relations project, relies on group representation in national governments and assesses the power of groups to co-determine the country’s future. Nevertheless, types of autonomy are also important factors in power relations, and they substantiate the minorities’ ability to self-govern. Territorially concentrated communal groups typically fight for territorial autonomies (TAs), while urban and dispersed minorities seek non-territorial autonomies (NTAs), such as ethnocultural self-governments. There is little quantitative data on NTAs, but their contribution to more peaceful inter-group relations is rarely challenged. The opposite is true for TAs. Majority groups in nation-states are reluctant to allow them, and scientific evidence thus far has not supported their effectiveness in mitigating inter-ethnic tensions and curbing secessionist tendencies. It appears that empirical studies of TAs are hindered by certain confounding factors that prevent clear-cut conclusions. First of all, regionally based minorities are more prevalent in developing countries, which tend to be less peaceful. The quality of autonomy and its overlap with other cleavages, such as an urban–rural divide, are also factors that may make a difference. This study explores a different confounder: the possibility that some minority groups may enjoy de facto regional autonomy even though nominal TAs exist. This may occur when a country’s administrative units are drawn around ethnic, religious, or linguistic settlement areas, and those administrative units also benefit from meaningful autonomy. An index constructed with the help of the QGIS software spatial join functions, which allowed for the quantification of the degree of overlap between the regional minorities’ settlement areas and the ADM01 units (https://gadm.org/), shows that minority self-government has, indeed, the same pacifying effect as other measures of political equality and minority protective policies. The study also explores comparisons between regional minorities and regional majorities, as well as the relationship between nationalism and administrative policies.